If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B + -8 + -6b + 10 = 0 Reorder the terms: -8 + 10 + B + -6b = 0 Combine like terms: -8 + 10 = 2 2 + B + -6b = 0 Solving 2 + B + -6b = 0 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + B + -2 + -6b = 0 + -2 Reorder the terms: 2 + -2 + B + -6b = 0 + -2 Combine like terms: 2 + -2 = 0 0 + B + -6b = 0 + -2 B + -6b = 0 + -2 Combine like terms: 0 + -2 = -2 B + -6b = -2 Add '6b' to each side of the equation. B + -6b + 6b = -2 + 6b Combine like terms: -6b + 6b = 0 B + 0 = -2 + 6b B = -2 + 6b Simplifying B = -2 + 6b
| ay-2=4 | | (14/5)+(74/45) | | 0.4(7x+14)=1.2-(x+2) | | -8k+6=94 | | 1/9y=5/6-1/9y | | 5n-3=-33 | | (37/5)*(2/9) | | P-20/9=6 | | (2t-4)-8(2t-4)+12=0 | | 17.2/k=4.3/4 | | 13-(28/5) | | 3x+10=x-5 | | 6=p-20/9 | | -2-(5/2) | | 3x+10=2x-5 | | 1/2x+1=7 | | 4x+8+10+32=180 | | 15/3.3=q/1.1 | | 2x^2-10x+4x-20=0 | | 6n^2+11n-2=0 | | 6x-20+x+40=180 | | (14/5)*2 | | -12x=108 | | 5y-6=34 | | (9+w)(4w+1)=0 | | 396=4(x-9) | | (y/3)^2=81 | | x(8-x)+6whenx=-2 | | -8(z+3)+3z= | | 4-3h=-2-6h | | 2/5+4 | | (14/15)*3 |